A PENGARUH KEPUTUSAN PEMBELIAN KARTU PAKET TELKOMSEL DARI PRESPEKTIF KUALITAS JARINGAN, CITRA MEREK DAN PROMOSI (Studi Kasus Pada Siswa SMK Brigjend Katamso II Medan): PENGARUH KEPUTUSAN PEMBELIAN KARTU PAKET TELKOMSEL DARI PRESPEKTIF KUALITAS JARINGAN, CITRA MEREK DAN PROMOSI (Studi Kasus Pada Siswa SMK Brigjend Katamso II Medan) - Pranata, Sungguh Ponten (Jurnal Mahkota Bisnis (Makbis), 2022)
The main purpose of this study is to analyze network quality, brand image, and promotion of the decision to purchase Telkomsel package cards in the student environment of Brigjend Katamso II Medan Vocational High School students. The approach used in this research is quantitative. The student population of Brigjend Katamso II Medan Vocational School is 479 people. The number of samples was determined based on the calculation of the Slovin formula with a tolerable error rate ranging from 5-1, then data collection using a questionnaire Data collection techniques using a questionnaire with a Likert scale. The results show that partially that network quality and promotion have an influence on purchasing decisions where the t-test of the two variables is greater than ttable (1.990). Meanwhile, the brand image variable does not influence the decision to purchase Telkomsel package cards at Brigjend Katamso II SMK Medan, Simultaneously these three variables have a significant influence on purchasing package cards at Brigjend Katamso II Vocational High School where Fcount > Ftable.